ENVIRONMENTAL COMPLIANCE AND ENFORCEMENT - Bhargava, Rashmi (International Journal of Research -GRANTHAALAYAH, 2015)
Each country faces a unique set of challenges and capacities to implement its environmental laws. However, there are fundamental elements in all countries that form the basis of effective environmental compliance and enforcement programs and of legal systems. These common principles, based on the collective knowledge and experience of the International Network for Environmental Compliance and Enforcement (INECE) and reflective of international good practice, may be used to improve national environmental compliance and enforcement programs. These principles are divided into five sections: (1) environmental results and shared responsibility, (2) goals and strategies, (3) good governance, rule of law and compliance, (4) structure and resources, and (5) continuous evaluation and improvement.